Distributive Justice in Post-Disaster Recovery Governance in Aceh: A Fiqh Siyāsah Perspective - Muhammad Firdaus; Muhammad Nurunabi; M. Anzaikhan (Prodi Tata Negara (Siyasah) IAIN Langsa, 2026)
The 2025 Aceh floods exposed persistent challenges of distributive justice in post-disaster recovery governance, particularly regarding unequal access to recovery resources among vulnerable groups. While previous studies have primarily focused on institutional effectiveness, coordination mechanisms, and the socio-economic impacts of disasters, limited attention has been given to distributive justice from the perspective of fiqh siyāsah (Islamic political jurisprudence). This study aims to identify patterns of inequality in post-disaster aid distribution, examine the concept of distributive justice within fiqh siyāsah, and reconstruct principles of equitable post-disaster recovery governance. This research employs a qualitative library research design combined with policy document analysis. Data were collected from government regulations, official reports of the National Disaster Management Agency (BNPB), scholarly publications, and credible media reports related to the 2025 Aceh floods. The findings reveal that recovery policies tend to prioritize physical reconstruction and formal economic sectors, while vulnerable groups such as smallholder farmers, traditional fishers, women, and persons with disabilities often face unequal access to assistance. Structural biases, bureaucratic complexity, and centralized decision-making further contribute to social and geographical disparities in resource distribution. Drawing upon the principles of al-'adālah, al-maṣlaḥah, al-amānah, al-syūrā, and ri'āyah al-ra'iyyah, this study proposes a normative model of post-disaster recovery governance that prioritizes vulnerable populations, strengthens ethical accountability, and promotes participatory decision-making. The study contributes to the development of fiqh siyāsah and disaster governance studies by offering a framework for advancing distributive justice in post-disaster recovery.